2006
DOI: 10.1158/1078-0432.ccr-06-0968
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Neurotensin-Mediated Interleukin-8 Production and Migration of HCT116 Human Colon Cancer Cells

Abstract: Purpose: Neurotensin, a gut tridecapeptide, acts as a potent cellular mitogen for various colorectal and pancreatic cancers that possess high-affinity neurotensin receptors. Cytokine/ chemokine proteins are increasingly recognized as important local factors that play a role in the metastasis and invasion of multiple cancers. The purpose of this study was to (a) determine the effect of neurotensin on cytokine/chemokine gene expression and cell migration in human cancer cells and (b) assess the effect of curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 47 publications
(55 reference statements)
4
72
0
1
Order By: Relevance
“…Previously, using the human intestinal cell line (HCT116, HT-29 and CaCO 2 ), it was shown that curcumin pretreatment inhibited and modulated gene expression of IL-8 in response to inflammatory cytokine exposure 20,21 . However, it was not investigated whether curcumin had a similar effect if given simultaneously with inflammatory inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using the human intestinal cell line (HCT116, HT-29 and CaCO 2 ), it was shown that curcumin pretreatment inhibited and modulated gene expression of IL-8 in response to inflammatory cytokine exposure 20,21 . However, it was not investigated whether curcumin had a similar effect if given simultaneously with inflammatory inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings suggest that ␤-catenin activation in response to PG is downstream of NF-B activation (45); thus activation of NF-B remains critical for measuring proliferative and antiapoptotic effects of PG. Besides PG, other gastrointestinal hormones, such as neurotensin (47) and amidated gastrins (43), also upregulate NF-B-mediated regulatory molecules such as IL-8. Thus growth-promoting and antiapoptotic effects of gastrointestinal hormones, via their cognate receptors, can be potentially mediated by the target gene products of activated NF-B pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Their results further concluded that IL-8 expression is negatively correlated to ER status and expressed preferentially in invasive cancer cells, which suggests a potential correlation between IL-8 expression and tumor progression and invasiveness. Another study also suggested that the overexpression of IL-8 associated with progression and metastasis of cancer cells in colon (37) (30). Curcumin also decreased IL-8 expression in human pancreatic cancer cell line (38).…”
Section: Curcumin Inhibits Expression Of Interleukins (Ils)mentioning
confidence: 95%
“…Curcumin inhibits the activation of AP-1 in colorectal (29) and breast cancer cells (14). Wang et al reported that neurotensin increased AP-1 DNA-binding activity and curcumin inhibited the neurotensin-mediated AP-1 activation in a colon cancer cell line (30). Curcumin inhibits signal transducer and activator of transcription 3 (STAT3).…”
Section: Potential Anti-migration Anti-invasion and Anti-colony Formmentioning
confidence: 99%